Effect of Tarekat Khalwattiyah-Samman on Fishermen's Work on The South Coast of South Sulawesi - Iskandar, Abdul Malik; Bahri, Syamsul; Masdar, Muhammad; Nonci, Nurmi; Azuz, Faidah; Harifuddin, Harifuddin (el Harakah: Jurnal Budaya Islam, 2023)
Coastal fishermen communities hold religious rituals as Sufism practices. One of which is Tarekat Khalwatiyah-Samman, which affects their daily work. This paper aims to identify the substance of the Khalwatiyah-Samman teachings. It deciphers the effect of this teaching on the work of fishermen on the south coast of South Sulawesi. This research is qualitative with social and empirical approaches. Data collection was done through in-depth interviews, observation, and literature study. It employed qualitative data processing and analysis. The results showed that the substance of the Khalwatiyah-Samman teachings lies in its three doctrines: the purification of the soul, the concept of the essence of God, and the concept of human essence. In addition, the influence of Khalwatiyah-Samman's teaching on the work of fishermen on the south coast of South Sulawesi is the emergence of attitudes in work such as complacency; God has determined everything, and they do not have a competitive spirit and spirit of achievement. Accordingly, the substance of the Khalwatiyah-Samman teaching is that God has determined all human actions, and humans only live it. Moreover, the effect of the Khalwatiyah-Samman teaching is to form an attitude of fatalism in fishermen or resignation. Masyarakat nelayan di wilayah pesisir memegang teguh ritual keagamaan sebagai praktik Sufisme. Salah satunya yaitu Tarekat Khalwatiyah-Samman yang berpengaruh terhadap pekerjaan sehari-hari nelayan. Tulisan ini bertujuan memahami substansi ajaran Tarekat Khalwatiyah-Samman. Penelitian ini mengungkap efek Tarekat Khalwatiyah-Samman terhadap pekerjaan nelayan di pesisir selatan Sulawesi Selatan Penelitian ini bersifat kualitatif dengan pendekatan sosial dan empiris. Pengumpulan data dilakukan melalui wawancara mendalam, observasi, dan studi literatur. Kajian ini menggunakan pengolahan dan analisis data kualitatif. Hasil penelitian menunjukkan bahwa ini substansi ajaran Tarekat Khalwatiyah-Samman terletak pada tiga doktrinnya yaitu penyucian jiwa, konsep esensi Ketuhanan dan konsep esensi manusia. Pengaruh tarekat Khalwatiyah-Samman terhadap pekerjaan nelayan di pesisir selatan Sulawesi Selatan adalah timbulnya sikap dalam bekerja seperti cepat puas, segala hal telah ditentukan oleh Tuhan, mereka tidak memiliki jiwa bersaing dan semangat berprestasi. Karena itulah substansi ajaran Khalwatiyah-Samman adalah semua perbuatan manusia telah ditentukan Tuhan dan manusia hanya menjalaninya. Adapun efek Tarekat Khalwatiyah-Samman adalah membentuk sikap fatalism pada nelayan atau kepasrahan.